Estimating an almost ideal demand system for red meat consumption in Libya Throughout the Year 2021 (A Case Study of the Municipality of Hay Al-Andalus) - Aljazeri, Najat Mustafa; Khairi, Said Yousif; Alwerfelli, Ragab Emhemed (Journal of agricultural, environmental and veterinary sciences, 2023)
The main objective of this study was to estimate the demand function for red meat consumption in the municipality of Hay Al-Andalus during the year 2021 by Almost Ideal Demand System (AIDS), to explain consumer behaviour through the seemingly unrelated regression estimation (SURE), The data came from the primary sources represented by questionnaire, and through imposing restrictions of adding up, homogeneity, symmetry, and negativity, the results of (AIDS) showed that there The high percentage of consumer spending on meat, where the largest percentage of sheep meat reached 31%, and this means that the Libyan consumer prefers this commodity to obtain his nutritional needs of animal protein, , while for cows, camels, poultry and fishes meat, it reached (18%, 8%, 28%,15%), respectively. The results of the price elasticity of demand for sheep, cows, camels, poultry and fishes' meat indicated inelastic through the obtained values (-0.03, -0.01, -0.51, -0.08, -0.06) respectively. Also there are found that there is a complementary relationship between sheep with cows, camels, poultry and fishes According to the cross-elasticities of demand, finally the expenditure elasticity showed that meat from sheep, cows, camels and poultry are considered to be inflexible and therefore essential commodities, Through the values obtained (0.39, 0.95, 0.45, 0.71), respectively, the demand for fish meat is elastic and is therefore considered a luxury good as it was estimated at (2.71), The study recommended expanding local red meat production by increasing investment in livestock production, and interest in increasing the production of poultry meat due to its low price compared to the prices of red meat and fish, in to be affordable for people with low incomes.
Keywords: consumption; red meat; almost ideal demand system (AIDS); elasticities; Hay Al-Andalus; Libya